ANALISIS PENERIMAAN TEKNOLOGI ELECTRONIC MEDICAL RECORD PADA RUMAH SAKIT UMUM DI JAWA BARAT - Oktri Mohammad Firadus (PROCEEDING STIMA)
Implementation of electronic medical record (EMR) in some hospitals, especially in West Java has entered the stage more advanced, which is not only applied to large hospitals, but has also been deployed in some hospitals of type C or D even at the level of the clinic. Resistance to new technology is certainly no doubt will always appear. It is caused by all stakeholders must involved through the adaptation process is not always easy. This research aims to determine the level of acceptance of EMR technology from the perspective of doctors (both general practitioners and specialists) at the General Hospital in West Java. The method used for data collection is by computer-based questionnaire using Google Forms and email sent to prospective respondents. Number of questionnaires distributed a total of 287, and the back and deserves to be treated as many as 73 pieces with a response rate of 25.44%. The research model used is a modified version of the Technology Acceptance Model (TAM). The final results of this research indicate that the usefulness factor being the biggest influence on the interest of doctors using EMR, while the ease of use factor is still the smallest influence.Keywords: doctors, electronic medical record, general hospital, TAM